Creativity in children of the Pre-Scholar Educational Institution Los Amautas, city of Sócota - Robles Valdivieso, Nelly Susana (2018)
The present study was established with the purpose of determining the level of creativity of the children of the Pre-scholar Educational Institution N ° 598 "Los Amautas" - Sócota, Cutervo. Considering that when carrying out the corresponding analysis of the problem it was found that there is a low level of development of creativity which limits the development of the learning process of the educational institution. The study design was a pre experimental type. There was a sample population of 47 boys and girls, who after receiving the stimulus, showed a significant degree of achievement of the level of development of creativity, since a large part of the study group that was at the low level had emigrated to the medium and high levels, becoming a very homogeneous group. From the verification process, we proceeded to analyze, interpret and discuss the results, concluding that the use of visual graphic strategies in the development of the learning sessions allowed to improve the level of creativity development in the children of the Educational Institution. Initial N ° 598 "The Amautas" in Sócota, province of Cutervo.